Mask-inspired moisture-transmitting and durable thermochromic perovskite smart windows - Sai Liu; Yang Li; Ying Wang; Yuwei Du; Kin Man Yu; Hin-Lap Yip; Alex K. Y. Jen; Baoling Huang; Chi Yan Tso (Nature Communications, 2024)
Abstract Thermochromic perovskite smart windows (TPWs) are a cutting-edge energy-efficient window technology. However, like most perovskite-based devices, humidity-related degradation limits their widespread application. Herein, inspired by the structure of medical masks, a unique triple-layer thermochromic perovskite window (MTPW) that enable sufficient water vapor transmission to trigger the thermochromism but effectively repel detrimental water and moisture to extend its lifespan is developed. The MTPW demonstrates superhydrophobicity and maintains a solar modulation ability above 20% during a 45-day aging test, with a decay rate 37 times lower than that of a pristine TPW. It can also immobilize lead ions and significantly reduce lead leakage by 66 times. Furthermore, a significant haze reduction from 90% to 30% is achieved, overcoming the blurriness problem of TPWs. Benefiting from the improved optical performance, extended lifespan, suppressed lead leakage, and facile fabrication, the MTPW pushes forward the wide applications of smart windows in green buildings.